Sosialisasi Pengurusan Nomor Induk Berusaha dan Sertifikat Halal bagi UMKM Desa Penusupan - Mungawanah, Fiatul; Fadlilah AM, Nilnal Muna; Nurul Khanifiiyah, Lulu Lestari; Fauziah, Muna (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
Penusupan Village is one of the villages located in Sruweng District, this village has various crafts and special foods. There are various businesses owned by Penusupan villagers. Many MSME actors in Penusupan Village do not yet have a production permit. As an effort to facilitate MSME actors, we held a socialization of NIB and Halal Certification, through the Online Single Submission (OSS) website in Penusupan Village. The purpose of this activity is to provide an understanding of the importance of official production permits. In addition, to accompany the creation to issuance of NIB. This socialization activity is carried out in three stages, namely; a) preparation, b) socialization, and c) mentoring. The results of this activity can issue three NIB directly on the spot. Then, continued mentoring and issuance of NIB outside the socialization activity. This activity has a positive impact on village MSME actors and supports the government's program to regulate administration for business actors.